Pericytes: jack-of-all-trades in cancer-related inflammation - Moro, Marianna; Balestrero, Federica Carolina; Grolla, Ambra A. (Frontiers in Pharmacology, 2024)
Pericytes, recognized as mural cells, have long been described as components involved in blood vessel formation, with a mere supporting role for endothelial cells. Emerging evidence strongly suggests their multifaceted roles within tissues and organs. Indeed, pericytes exhibit a remarkable ability to anticipate endothelial cell behaviour and adapt their functions based on the specific cells they interact with. Pericytes can be activated by pro-inflammatory stimuli and crosstalk with immune cells, actively participating in their transmigration into blood vessels. Moreover, they can influence the immune response, often sustaining an immunosuppressive phenotype in most of the cancer types studied. In this review, we concentrate on the intricate crosstalk between pericytes and immune cells in cancer, highlighting the primary evidence regarding pericytes' involvement in primary tumour mass dynamics, their contributions to tumour reprogramming for invasion and migration of malignant cells, and their role in the formation of pre-metastatic niches. Finally, we explored recent and emerging pharmacological approaches aimed at vascular normalization, including novel strategies to enhance the efficacy of immunotherapy through combined use with anti-angiogenic drugs.Eberth in 1871 and later Rouget in 1873 first described a subpopulation of cells as a cluster of contractile cells that extend their projections encircling the capillaries (Eberth et al., 1871;Rouget 1874). Some years later, Zimmerman named them as "pericytes", simply on the bases of their localization long the vasculature, bypassing their many features too complicated to include in a unique name. It is well established that these are multitasking cells, able to acquire different roles depending on the tissue or organ in which they are found and, on the cells, they collaborate with. In the last few years, the need of knowledge on pericytes is gaining exactly as, several years ago, astrocytes started to be considered active cells in the brain and not simply structural tools for neurons. Indeed, recent data described pericytes as essential orchestrators that